13-Year Compulsory Education: A Strategic Step Towards Equitable Access to Children's Education in Indonesia - Dusalan, Dusalan (LP2M IAI Al-Khairat Pamekasan, 2025)
The 13-Year Compulsory Learning Program is a strategic step taken by the Indonesian government to improve the quality of human resources by expanding access to education to the upper secondary level. This program is a continuation of the 9-Year Compulsory Learning program which only covers basic education, and aims to provide wider opportunities for every child in Indonesia to get an adequate education in the global and digital era. Despite facing major challenges, such as limited educational facilities and infrastructure, social and cultural barriers, and administrative problems in education management, the implementation of this program is expected to have a significant positive impact. The expected impacts include an increase in the participation rate of education at the upper secondary level, a decrease in the youth unemployment rate, and the creation of a smarter, empowered, and more productive society. The success of this program depends on strong cooperation between the government, the private sector, and the community, as well as the active role of all parties in supporting this policy through adequate budget allocation, equitable distribution of educational infrastructure, and empowerment of educators. The 13-Year Compulsory Learning Program has the potential to be a major driver in creating equality of educational opportunities and realizing the ideals of a fairer and more prosperous Indonesian independence.